Absent voices of the students and belittled bodies. Spaces of appearance as a chance for inclusión (Práxis Educativa, 2024)
Dropout has increased, turning into a problem that has become a field of study. Various/Some studies have stressed the need for developing the conceptualisation of dropout in an easier way to understand and give visibility to subjects and what they narrate from their experience. The objective of this paper is to provide another way of understanding the implicit nature of dropout using "spaces of appearance" (following Arendt and Butler) as a tool for analysis. It is analysed: a) the invisibilization of students analyzed from what we call "spaces of disappearance", which promote dropout, and b) “spaces of appearance” which make possible the recognition of the subjects with agency and as epistemic subject. It is concluded that spaces of appearance are favourable to both the existence of inclusive schools and the avoidance of dropout as a structural phenomenonKeywords: Dropouts. Epistemic Injustice. Spaces of appearance.